Role of resilience in selection of R factors for an RC building - Prasanth, S.; Ghosh, Goutam (Frontiers in Built Environment, 2022)
In the seismic design of a reinforced concrete building, taking the appropriate response reduction factor (R) plays a vital role in the building’s seismic response. Indian Standard (IS: 1893-2016) provides R values of 3 and 5 for Ordinary Moment Resisting Frame (OMRF) and Special Moment Resisting Frame (SMRF) respectively. As R factors are used to incorporate the non-linearity in the building, the selection R factor should be based on the building’s performance in terms of resilience. Since Indian Standard (IS) does not provide any clause on the background in the selection of R factors for the design aspects, the study emphasizes the appropriate selection of R factors with respect to the building’s functionality, performance level and resilience. In this study, a high-rise building is designed with various R factors (R=3, 4, 5 and 6). To estimate the building’s functionality, five different recovery paths (RP-1 to RP-5) which match the real scenario were used. The response of the building in each case was observed at two design levels namely Design Basic Earthquake (DBE) and Maximum Considered Earthquake (MCE). The variation in the ductility demand, performance level and resilience at each building case at each design level was observed. The R factor is used to obtain the lateral design force at the design basic earthquake by reducing the actual base shear coming on the structure. The reduction in the lateral design force with maximum R yields high ductility demand and high loss of resilience. The result shows that the considered building can be designed with a maximum R of 6 since the building’s resilience is almost 50% hence recovery is possible at a high cost. It is observed that the performance level of the building at R=6 lies at CP-C level at MCE design level. With consideration of the building’s resilience and performance level aspects, the maximum R factor was found to be 6. This helps the stakeholder and designer in the selection of R based on the requirement of building functionality, performance level and resilience